Compilation of multi-source historical data on Mediterranean sponge fisheries - Fourt, Maïa; Faget, Daniel; Pérez, Thierry (Aix-Marseille University, CNRS, IRD and Avignon University, 2021)
Sponges are benthic animals that live attached to the ocean bottom and feed by filtering seawater. In the Mediterranean Sea there are many species, some of which have been harvested during centuries for commercialization. These horny sponges were harvested using techniques that varied in time and space. Sponge production in the Mediterranean Sea peaked at the end of the 19th century, and a second time, after the Second World War, when approximately 300 tons were produced per year. In recent years, Mediterranean sponge production has declined to barely a few tons per year. The objective of the SACOLEVE program (Spatial and temporal Adaptation of a traditional Mediterranean fishery facing Regional Change: COmbining history and ecoLogy to study past, prEsent and future of sponge HarVEsting) was to (i) obtain a full picture of the sponge production decrease and (ii) understand the underlying reasons explaining the temporal sponge production variations. In the frame of this program, a PhD thesis entitled "Histoire de la pêche des éponges en Méditerranée, et son adaptation récente au changement régional" (Mediterranean sponge fishing history and its recent adaptation to regional change) was dedicated to this research topic. Information from numerous archives, grey literature, published articles and fishermen interviews were collected and stored in an original Access 2013 database. This tool answered the needs of labelling, sorting, homogenizing and cross-referencing large quantities of historical information on sponge fishing in the Mediterranean. Data, mainly from the Mediterranean countries, span the period from the 18th century to 2019. They concern geographic distribution of commercial sponge populations, commercial yearly movements (production, export, import) of sponges, and detailed sponge fishing efforts for the main sponge-producing countries and smaller sponge fishing communities. The data submitted here represent a partial extraction of the database used for the PhD thesis.
Keywords: adaptation; AMU; Biodivmex; CNRS; commercial sponges; environmental changes; IMBE; IRD; Mediterranean Sea; OT-Med; SACOLEVE; small-scale fishery; TELEMME